What do we know about Torso Protectors and Foot Wears – A Review for COVID-19 Pandemic and Possible Future Epidemics - Valikhanlou, Nayyereh; Meshkini, Mohammad; Meshkini, Fatemeh; Jalilvand, Hadi (International Journal of Coronaviruses, 2021)
Personal Protective types of Equipment (PPE) are needed for everybody who would be in danger of threatening state; the COVID-19 pandemic raised the need and global demand for PPE, one of the most used and required equipment are gowns, coveralls, and torso protectors; which their shortage of supply raised the cost globally too. This review article gathered the guidelines and recommendations from manufacturers, international organizations, and self-experiments of authors for these utilities. And, provides recommendations on the level of protection needed for each condition.
Keywords: Gown; Coverall; SMS; breathable clothes; Spunbond; Non-woven fabric.